Real time water delivery management and planning in irrigation and drainage networks - Karami, Vahid, author; Bahrami, Roghayeh Samadi, author; Dalir, Ali Hosseinzadeh, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
This paper focuses on delivery and demand management in irrigation and drainage networks as the largest water resource consumer. A model is developed for water demand management in irrigation networks. The model is capable of predicting actual water requirements in every field blocks and produces water delivery schedule for all network elements. In this model, planning water delivery schedule in irrigation network is accomplished by considering three important factors including crops irrigation calendars, water distribution method, and canals hydraulic conditions and performance. The model incorporates CANAL ROTATION & SEMI DEMAND method for water distribution in canals. Due to sizable quantity and spatial and temporal variations of required data and the necessity for updating the results in real time operation, all the required data are classified, stored and managed in a database system. The developed model is also capable of planning water delivery in canals upon sound simplifications of irrigation planning regarding proper water distribution criteria. In dry periods, the developed model compares actual required water with available water resources and modifies quantity and/or delivery time considering amount of available water. The model is incorporated in planning water delivery management system for RMC lot (4500 ha) in Irrigation and drainage Scheme (Aji-Chai) located in Tabriz plain, East Azerbaijan, Northwest of Iran.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.